(untitled) (Research Journal, 2023)
This paper reports the findings of the study that attempted to find out the reproductive health problems faced by the tribal women of Phidim Municipality, Panchthar. Altogether 160 tribal women of Phidim municipality ward no. 10 were selected using simple random sampling technique. Interview schedule was used for the data collection. Questions for the interviews were prepared in order to collect essential data from tribal women, which were applied to the sampled population The findings revealed that majority of the tribal woman reported various problems related to their reproductive health such as pain in lower stomach and vaginal discharge with bad smell from related sex organs. Continuously pain in lower stomach related to placenta is seen major problems of respondents after having child. Over bleeding, mental tension was seen the main problems during menstruation. Most of the respondents (70%) were unknown about contraceptive devices however among them 52.83 percent of the women were found aware of the usage of contraceptives with the access to social media and communication media.